Material Flux From the Rings of Saturn Into Its Atmosphere. Issue 19 (4th October 2018) - Perry, M. E.; Waite, J. H.; Mitchell, D. G.; Miller, K. E.; Cravens, T. E.; Perryman, R. S.; Moore, L.; Yelle, R. V.; Hsu, H.‐W.; Hedman, M. M.; Cuzzi, J. N.; Strobel, D. F.; et al.
Abstract: During Cassini's final, spectacular months, in situ instruments made the first direct measurements of nanoparticles, finding an exceptionally large flow from the rings into Saturn's atmosphere. Cassini's Ion and Neutral Mass Spectrometer measured material in three altitude bands and found a global‐integrated flux of 2–20 × 10 4 kg/s that is dominated by hydrocarbon material <10 4 u. Ranging from clusters of a few molecules to radii of several nanometers, nanoparticles are ubiquitous throughout Saturn's rings but embedded in the regolith of larger particles and not detectable as independent particles using remote observations. The smallest nanoparticles are susceptible to atmosphere drag by Saturn's tenuous exosphere that reaches the inner edge of the D ring. The unsustainable large flux suggests a recent disturbance of Saturn's inner ring material, possibly associated with the clumping that appeared in the D68 ringlet in 2015. Plain Language Summary: For 40 years, calculations based on remote observations indicated that Saturn's magnetic field carries ions and charged particles from the rings to the midlatitudes of Saturn. In Cassini's last few months of life, direct, in situ measurements found that 10 tons/s of molecules and particles smaller than two nanometers are streaming along the plane of the rings into Saturn's atmosphere by another process: atmospheric drag. Saturn's extended atmosphere reaches the inner edge of Saturn's rings and extracts neutral particles less than one thousandth the thickness of a human hair by slowing them down until they fall into Saturn. Surprisingly, the flux is a hundred times larger than past predictions, and at least half of the material is hydrocarbon, which comprises less than 5% of the water ice‐dominated rings. Cassini's data also show that the influx varies at least a factor of 4 and may be linked to clumps that appeared in 2015 on D68, the ringlet on the inner edge of the rings. These newly discovered particles and processes alter the evolutionary landscape of the rings and provide an exciting, rich field for future research aimed at understanding the origin and history of the rings. Key Points: Atmospheric drag, an interaction newly applied to Saturn and its rings, extracts >10 4 kg/s of neutral nanoparticles from Saturn's rings Molecules and particles <2 nm in radius are preferentially transported by atmospheric drag Neutral, nanometer‐sized hydrocarbon material is currently the largest mass loss from Saturn's rings